Intrahospital Handovers before and after the Implementation of ISBAR Communication: A Quality Improvement Study on ICU Nurses' Handovers to General Medical Ward Nurses - Marit Hegg Reime; Linda Skaug Tangvik; Mats Aleksander Kinn-Mikalsen; Tone Johnsgaard (MDPI AG, 2024)
Background: Research finds a lack of structure as well as varying and incomplete content in intrahospital handovers. This study aimed to improve intrahospital handovers by implementing structured ISBAR communication (identification, situation, background, assessment and recommendation). Methods: This quality improvement study was conducted observing 25 handovers given by nurses from the intensive care unit to nurses from general medical wards at baseline and after the implementation of the ISBAR communication tool. The 26-item ISBAR scoring tool was used to audit the handovers. In addition, the structure of the ISBAR communication and time spent on the handovers were observed. Results: There were no significant improvements from baseline to post-intervention regarding adherence to the ISBAR communication scoring tool. The structure of the handovers improved from baseline to post-intervention (p = 0.047). The time spent on handovers declined from baseline to post-intervention, although not significantly. Conclusions: The items in the ISBAR communication scoring tool can act as a guide for details that need to be reported during intrahospital handovers to strengthen patient safety. Future research calls for studies measuring satisfaction among nurses regarding using different handover tools and studies using multifaceted training interventions.